Pengaruh Personal Characteristics Pengusaha UMKM Melalui Entrepreneurial Orientation Terhadap Kinerja Bisnis UMKM Di Kota Pasuruan - Haryono, Haryono; Muliatie, Yurilla Endah (STIE Mahardhika, 2017)
Pasuruan has some excellent products produced by UMKM spread in Pasuruan City area. One of them is furniture which is commonly found in the South of Pasuruan City e.g Kelurahan Bukir, Kelurahan Sebani, Kelurahan Krapyakrejo, Kelurahan Randusari, Kelurahan Gentong, Kelurahan Petahunan and Kelurahan Karangketug. Labor is largely composed of families and neighbors around the area so that the industry can have a significant impact on improving the economy of local communities. Have a pretty good prospect to develop. The existence of micro, small and medium businesses in the Pasuruan city is a strategic industry that becomes an opportunity for improvement of the regional economy. Micro, small and medium businesses (UMKM) in addition can absorb a very large number of workers which means reducing the unemployment rate, as well as economic development. Based on the background that has been described above, the researcher choose the title of this study as follows: